Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1177/1534650111401016
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Cognitive Therapy for Problem Gambling

Abstract: This article describes treatment of a female problem gambler using mindfulness-based cognitive therapy (MBCT). The treatment protocol was adapted for problem gamblers from the manualized MBCT intervention developed by Segal, Williams, and Teasdale. Gambling behavior and mindfulness practice were monitored using daily diary entries maintained by the participant. The Beck Anxiety Inventory, Beck Depression Inventory—II, and the Five Facet Mindfulness Questionnaire were administered at pretreatment, posttreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 60 publications
5
43
0
Order By: Relevance
“…According to Shonin et al (2013b) andde Lisle et al (2012), little research has been conducted on the use of mindfulness for problem gambling treatment. As noted above, there have been two case studies published about mindfulness (see, de Lisle et al, 2011) and two research studies that evaluated DBT (Korman et al, 2008;Christensen et al, 2013). The study by Christensen et al (2013) reported that the intervention resulted in significant improvements in the participants' level of dispositional mindfulness.…”
Section: Implications Of Our Study For Problem Gamblingmentioning
confidence: 99%
“…According to Shonin et al (2013b) andde Lisle et al (2012), little research has been conducted on the use of mindfulness for problem gambling treatment. As noted above, there have been two case studies published about mindfulness (see, de Lisle et al, 2011) and two research studies that evaluated DBT (Korman et al, 2008;Christensen et al, 2013). The study by Christensen et al (2013) reported that the intervention resulted in significant improvements in the participants' level of dispositional mindfulness.…”
Section: Implications Of Our Study For Problem Gamblingmentioning
confidence: 99%
“…Researchers discovered a negative association between dispositional mindfulness and gambling severity in problem gamblers, 17 thought suppression, 18 and psychological distress. 19 Several recent case studies have verified that mindfulness can lead to a clinically significant alteration in patients with gambling problems. 16,[19][20][21][22] Beyond gambling addiction, a single case study conducted by Shonin et al 14 have investigated workaholism, treated with a mindfulness approach, in which a patient was successfully treated using Meditation Awareness Training.…”
Section: Introductionmentioning
confidence: 99%
“…19 Several recent case studies have verified that mindfulness can lead to a clinically significant alteration in patients with gambling problems. 16,[19][20][21][22] Beyond gambling addiction, a single case study conducted by Shonin et al 14 have investigated workaholism, treated with a mindfulness approach, in which a patient was successfully treated using Meditation Awareness Training. 23 Important improvements after the training were also observed for relevant variables such as: psychological distress, sleep quality, work activities during free time, hours of work, and job performance.…”
Section: Introductionmentioning
confidence: 99%
“…Within mental health and addiction treatment settings, mindfulness-based interventions (MBIs) are generally delivered in a secular eight-week format and invariably comprise the following: (i) weekly sessions of 90-180 minutes duration, (ii) a taught psycho-education component, (iii) guided mindfulness exercises, (iv) a CD of guided mindfulness and/or meditation exercises to facilitate daily self-practice, and (v) varying degrees of one-to-one discussion-based therapy with the program instructor. Examples of MBIs used in behavioral addiction treatment studies include MindfulnessBased Cognitive Therapy, Mindfulness-Enhanced Cognitive Behavior Therapy, Mindfulness-Based Relapse Prevention, Mindfulness-Based Stress Reduction, and Meditation Awareness Training [4][5][6].…”
mentioning
confidence: 99%
“…Recent clinical case studies have demonstrated that weekly mindfulness therapy sessions can lead to clinically significant change in problem gambling individuals. Published case studies include: (i) a male in his sixties addicted to offline roulette playing [10], (ii) a 61-year old female (with comorbid anxiety and depression) addicted to slot machine gambling (treated with a modified version of Mindfulness-Based Cognitive Therapy) [6], and (iii) a 32-year old female (with co-occurring schizophrenia) addicted to online slot-machine playing (treated with a modified version of Meditation Awareness Training) [11]. Additionally, a recent controlled study showed that problem gamblers that received Mindfulness-Enhanced Cognitive Behavior Therapy demonstrated significant improvements over wait-list control participants in levels of gambling severity, gambling urges, and emotional distress [5].…”
mentioning
confidence: 99%